Expression and modulation of complement receptor 2 (CR2/CD21) in the pathophysiology of rheumatoid arthritis - Dash, Rozaleen; Kumar, Uma; Kanjilal, Maumita; Das, Nibhriti (International Journal of Research in Medical Sciences, 2017)
Background: The involvement of B cells, complement activation and subsequent immune complex deposition has been implicated in the pathogenesis of rheumatoid arthritis (RA). Although the reduced expression of complement receptor 2 (CR2, CD21) on the B cells of RA patients is known for long, we aimed at determining the modulation and expression of CR2 on PBMC of healthy individuals and RA patients. Methods: Sixty controls and 57 RA patients were enrolled. PBMC-CR2 transcript levels were correlated with the levels of C3, C3d and circulating immune complexes (CIC) in controls and patients and with DAS28 in patients only. CIC levels were determined by PEG precipitation, C3 levels by nephlometry and C3d levels were determined by enzyme linked immunosorbent assay (ELISA). Sixteen patients were recruited for 6 months follow up studies of transcript levels of PBMC correlated with DAS28 score. Appropriate statistical methods were used for the analyses of data. Results: PBMC- CR2 transcript levels were declined in patients as compared to controls. PBMC-CR2 levels correlated negatively with DAS28 score. DAS28 correlated positively with levels of CIC, C3 and C3d. Levels of PBMC -CR2 increased in patients with decline in DAS28 scores in 6 months follow-up patients. Conclusions: Low level of CR2 expression in patients may, thus, contribute significantly to the pathological manifestation of RA. Cause-effect relationships of the up regulation of CR2 on improvement of health condition with the pathophysiology of RA and their importance as putative disease markers is being confirmed.